Economic valuation of a plan to avoid the loss of basic and industrial cultures in oaxaca, mexico - López, Maribel (2017)
In Mexico, the availability of raw materials to supply the agri-food industry with basic grains and other products has variations from one year to the next. One of the reasons that affects this supply is the frequent presence of meteorological phenomena suchas hurricanes or high intensity rainfall, which directly affect agricultural crops, causing losses of 50 to 80% of the harvest; In livestock activity, they represent losses of 30% of the livestock. For this reason, the objective of this research was to make an economic valuation through the benefit/cost ratio of a flood prevention plan in Manialtepec, Oaxaca, México, for which surveys and interviews were conducted directly with Producers and authorities of the place.  The economic benefits, which in this case are the damages avoided, were estimated obtaining the total cost of damage caused by hurricanes in 2014; While the costs of the plan were estimated by quantifying the total amount of the proposed prevention works. The benefit/cost ratio for this project was 2.3, taking into account a 30-year period of useful life of the works; The estimated benefits were $137,431, 032.00 pesos and costs $59,849, 325.00 pesos. Therefore, according to the economic estimates made, it was concluded that the implementation of the hurricane damage prevention plan is viable and cost-effective, and would mitigate the shortage of raw materials, such as maize, beans, coffee, cattle, Among others, guaranteeing the supply of the food industry in the region.